Controllability Criterion of Nonlinear Dynamical Systems - Mazakov, T. Zh.; Jomartova, Sh. A.; Zhakypov, A. T.; Tursynbay, A. T. (Journal of Mathematics, Mechanics and Computer Science, 2015)
This paper devotes to controllability of nonlinear dynamical systems. Main result of this work is controllability criteria, received on the basic of application of the interval analysis.